Multisegment Targeting Analysis of Gojek and Its Positioning as a Daily-Life Super: Penelitian - Adiba Nurkhafiza; Helga Irena Pratiwi; Yulianti; Liza Nora; Tria Patrianti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The growth of Indonesia’s digital economy has driven the emergence of integrated application-based ecosystems operating within a multi-sided platform (MSP) structure. Gojek has become one of the leading actors that successfully transformed from a ride-hailing service into a super app encompassing various daily needs. This study aims to analyze Gojek’s multisegment targeting strategies toward four key groups users, driver-partners, micro small and medium enterprises (MSME) merchants, and business partners and to explain how these strategies contribute to Gojek’s positioning as an “everyday life super app.” The research employs a descriptive explanatory qualitative approach through documentation study, application observation, and literature analysis. The findings show that Gojek applies differentiated targeting strategies for each segment, yet all segments operate within interdependent relationships that generate cross-side network effects. These targeting strategies strengthen ecosystem stability and support the organic expansion of services. Moreover, consistent user experience, seamless feature integration, and adaptation to local contexts reinforce Gojek’s positioning against competitors. The research enriches digital marketing literature related to the application of segmentation, targeting, and positioning (STP) in multisided platforms and provides practical implications for technology companies aiming to develop integrated service ecosystems. This study emphasizes that the success of a super app is not merely determined by service diversification but by the ability to holistically and sustainably manage a multisegment ecosystem.